A COMPARATIVE ANALYSIS OF SPEECH ACT THEORY APPLIED TO THE ENGLISH AND UZBEK LANGUAGES, CONSIDERING BOTH SEMANTIC AND STRUCTURAL LEVELS - Mohinur, Axmadjonova (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This article examines the application of speech act theory to the English and Uzbek languages, focusing on semantic and structural differences and similarities. Speech acts, as defined by Austin and further developed by Searle, form a crucial component of communication. This study investigates how these acts manifest across two distinct linguistic and cultural systems, providing insights into pragmatics, language use, and cultural context.